2010
DOI: 10.1007/s11999-009-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Increases the Risk for Rotator Cuff Tears

Abstract: There is little available evidence regarding risk factors for rotator cuff tears. Cigarette smoking may be an important risk factor for rotator cuff disease. The purpose of this study was to determine if cigarette smoking correlates with an increased risk for rotator cuff tears in patients who present with shoulder pain. A questionnaire was administered to 586 consecutive patients 18 years of age or older who had a diagnostic shoulder ultrasound for unilateral, atraumatic shoulder pain with no history of shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
2
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 18 publications
4
128
2
9
Order By: Relevance
“…Baumgarten et al (8) observed a strong association between smoking and RC disease. The authors found that this association is dose-dependent and smoking-time-dependent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Baumgarten et al (8) observed a strong association between smoking and RC disease. The authors found that this association is dose-dependent and smoking-time-dependent.…”
Section: Discussionmentioning
confidence: 97%
“…A higher incidence of RC tears is (are) observed, as well as the possibility of late diagnosis in smoking patients (7)(8)(9) , but the literature is controversial as to the extent to which smoking influences the postoperative outcome of RC repair (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Baumgarten et al [20] conducted a study of 375 patients with RCTs confirmed by ultrasound (of all patients presenting with shoulder pain in general, of all demographics and characteristics). Of these 375 patients, 232 (62%) were smokers with a mean 23.4 years of smoking 1.25 packs per day and 30.1 mean packyears.…”
Section: Smokingmentioning
confidence: 99%
“…33) Indications for reverse total shoulder arthroplasty are; First, who have old age, multiple underlying diseases such as diabetes mellitus, smokes or chronic rotator cuff tear lesion that is less capable to be healed, painful symptoms under the physical examinations, less than 90 degree of forward flexion and retracted rotator cuff without upper migration of humeral head under the MRI. [37][38][39][40][41][42][43][44] Second, patients who have massive rotator cuff tear with pseudoparalysis, pain and apparent anterosuperior escapse of humeral head are also indicated. 19,[45][46][47] But patients who have massive rotator cuff tear with abnormal function of deltoid are contraindicated for reverse total shoulder arthroplasty.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%